Serum Proteomics in African American Female Patients With Irritable Bowel Syndrome: An Exploratory Study. Issue 3 (May 2018) - Weaver, Kristen R.; Melkus, Gail D' Eramo; Fletcher, Jason; Henderson, Wendy A.
Abstract : Background: Sex and subtype differences within patients with irritable bowel syndrome (IBS) complicate the understanding of disorder pathogenesis and hinder the design of efficacious, therapeutic interventions. Objectives: The aims of this study were to harness the power of shotgun proteomic analysis, identify circulating proteins that differentiate African American female patients with IBS from healthy controls (HC), and gain biological insight on symptomatology. Methods: Serum proteome analysis was performed upon a cohort of overweight, African American female participants with constipation predominant IBS symptoms ( n = 5) and HC ( n = 5), matched on age, sex, years of education, body mass index, and 11 physiological markers. Tandem mass tags for multiplexed proteomic analysis were performed, incorporating reverse-phase liquid chromatography and liquid chromatography-tandem mass spectrometry. Results: Participants with IBS did not differ from HC in demographics, clinical characteristics, or initial proteomic analysis. Nested case control analysis of six samples (IBS: n = 3, HC: n = 3), hierarchically clustered into two main groups, with 12 out of 1, 317 proteins significantly different in levels of expression: TGFβ1, PF4V1, PF4, APP, MMP9, PPBP, CTGF, SRGN, THBS1, WRN, LTBP1 (Isoform 3), and IGLV5-48. Top associations of identified proteins in DAVID and STRING resources (upregulated in HC vs. IBS) involve platelet alpha granule lumen, platelet activation/degranulation, extracellular region, and secretion by cell. Discussion: Differentially expressed proteins between participants with IBS and HC involving platelet-related associations prompt inquiry as to differences in serotonergic signaling, inflammatory or immunomodulatory mechanisms underlying IBS symptomatology. Although preliminary and requiring validation in larger cohorts, these findings bear relevance to understanding pathogenic processes of IBS and biological effects of the disorder.